TOEFL (TEST OF ENGLISH AS A FOREIGN LANGUAGE) TEST PLUGIN UNTUK MOODLE - Leovin, Leovin; Ary Esta Dewi Wirastuti, Ni Made; Oka Saputra, Komang (Jurnal SPEKTRUM, 2022)
TOEFL (Test of English as a Foreign Language) is a test used to measure a person's English proficiency. Generally, the TOEFL test is used as one of the requirements to graduate at domestic universities, to enter universities abroad, or to work in a country. In this research, the LMS (Learning Management System) was used for implement the TOEFL. LMS is an application system that was developed specifically to manage online class (e-learning), and share subject matter. Moodle (Modular Object-Oriented Dynamic Learning Environment) is an LMS that is usually used in online learning activities. The results of this research that the TOEFL was successfully created as a Moodle plugin and according to the SUS (System Usability Scale) test that has been calculated, it got a score of 89, indicating this application has a high level of feasibility.